2003
DOI: 10.1034/j.1600-0412.2003.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the glycoproteic meshwork of cervical mucus in the mechanism of sperm orientation

Abstract: The study confirms that there is a close relationship between the three-dimensional arrangement of the mucus framework and the ability of spermatozoa to move rapidly in a given direction. The high resolution and three-dimensional aspect of SEM micrographs support the correlation of sperm orientation with current data on rheologic properties of biologic hydrogels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…They found that migration of buck spermatozoa was highly correlated to velocity parameters (VCL and VAP, p < 0.01), and just correlated to VSL (p = 0.05), but kinematic parameters were not correlated with migration in bovine cervical mucus (p > 0.10). The microstructure of mucus as seen in the cervical channel seems to be maintained by its aspiration into flat capillary tubes (Chrétien 2003). The particular ability of spermatozoa to migrate in epithelial mucus seems to rely, at least partially, in the hydrodynamic force as shown by specific kinematic parameters, where VCL and VAP appeared as the most important in rams.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that migration of buck spermatozoa was highly correlated to velocity parameters (VCL and VAP, p < 0.01), and just correlated to VSL (p = 0.05), but kinematic parameters were not correlated with migration in bovine cervical mucus (p > 0.10). The microstructure of mucus as seen in the cervical channel seems to be maintained by its aspiration into flat capillary tubes (Chrétien 2003). The particular ability of spermatozoa to migrate in epithelial mucus seems to rely, at least partially, in the hydrodynamic force as shown by specific kinematic parameters, where VCL and VAP appeared as the most important in rams.…”
Section: Discussionmentioning
confidence: 99%
“…1989; López‐Gatius et al. 1994; Chrétien 2003; Rutllant et al. 2005) as does media with different viscoelastic properties (Suarez and Dai 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations